O currículo de ciências via tema gerador: desafios docentes na Escola Cabana - RESQUE, Marciléa Serrão (2005)
This research paper seeks for the comprehension and analysis of how science teachers who work in municipal schools which adopt the <<Escola Cabana>> project deal with the process of their curriculum proposals elaboration involving generating themes. This work looks for identifying the factors involved in that elaboration, important challengers and dilemmas in an inovative educal proposal. Relating to the methodology orientation, I considered the qualitative approach to support the resech. As this document is related to a determined educational reality the << Escola Cabana>> - I selected five science teachers as reseach subjects: they act in schools that oficially follow these educational proposal orientations, and I also selected a technician of the municipal education administration. The data was obtained from two main sources: reading oficial documents about the project and semi-structured interviews with science teacher in education institutions involved in the project. The data analysis made from subject teachers statements helped to comprehend the teachers perceptions and actions about the proposal to elaborate a curriculum based on generating themes. Confronting the reality of working inside a different education proposal, teachers narrate their limitations, advances and retreats in their curriculum practices. The profissional isolation, the perception and personal interpretation of the project orientations and the difficulties in breaking curriculum traditions were points discussed by the subject teachers in a direct or indirect way in their statements. Besides, the difficulties and dilemas in working new things with knowledge coming from students daily life, therefore, they work with practices which confront the ones from the graduation period and professional acting. The perception that teacher need to size up their involvement in curriculum woks again, recovering the competence of elaborating curriculum proposals closely related to the teaching process of elaborating curriculum proposals related to the educational reality, ocurred through the research development. Assuming the curriculum proposals process, understanding the curriculum role and centrality in the teaching area are ways that lead to more conscious curriculum and educational practices.